The Relative Age Effect and Under-21 Irish Association Football: A Natural Experiment and Policy Recommendations - Butler, David; Butler, Robert (Economic & Social Studies, 2015)
A relative age effect refers to the presence of a bias towards relatively older children assembled collectively within a selection year. We consider this in association football (soccer) for Republic of Ireland under twenty-one international footballers over two intervals: from November 1981 to November 1994 and from September 2007 to May 2013. As the registration date for organised soccer in Ireland changed between both periods, these intervals provide scope for a natural experiment to test for a shifting relative age effect. The study confirms the existence of a relative age effect, with a selection bias toward players born in the earlier months of the registration year for both intervals.